2013
DOI: 10.1007/s00005-013-0258-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Significance of Cytotoxic Cell Subsets in Biopsies of HCV-Infected Human Livers

Abstract: Chronic viral hepatitis C still remains the clinical challenge. Attempts of the immune system to cope with this infection are unsatisfactory. There is a conviction that the main site of interaction between virus (Hepatitis C virus, HCV) and immune system is in situ, i.e., in liver. Natural killer (NK) cells appeared relevant in the acute hepatitis. Less is known about the immune response in the chronic HCV infection. The aim of this study was to evaluate the prevalence of various cytotoxic cell subsets in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…KIR2DS4 gene, without determining full-length versus deleted variants, was found protective against HCV infection, elevated ALT levels and cirrhosis in Argentinian Caucasians (Paladino et al 2007 ) and in exposed intravenous drug users of Puerto Rican descent (Zúñiga et al 2009 ). We have also described recently a correlation between ALT and AST levels before therapy and expression of another activating NK cell receptor, NKG2D, in livers of HCV-infected individuals (Mozer-Lisewska et al 2014 ). In that study, we found a higher abundance of NKG2D + cells than that of CD56 + cells in liver infiltrates, which suggests that other cells, presumably T cells, expressed NKG2D in addition to NK cells.…”
Section: Discussionmentioning
confidence: 80%
“…KIR2DS4 gene, without determining full-length versus deleted variants, was found protective against HCV infection, elevated ALT levels and cirrhosis in Argentinian Caucasians (Paladino et al 2007 ) and in exposed intravenous drug users of Puerto Rican descent (Zúñiga et al 2009 ). We have also described recently a correlation between ALT and AST levels before therapy and expression of another activating NK cell receptor, NKG2D, in livers of HCV-infected individuals (Mozer-Lisewska et al 2014 ). In that study, we found a higher abundance of NKG2D + cells than that of CD56 + cells in liver infiltrates, which suggests that other cells, presumably T cells, expressed NKG2D in addition to NK cells.…”
Section: Discussionmentioning
confidence: 80%
“…The authors, therefore, concluded that there is a general antigen-nonspecific activation of the resident memory CD8+ T cells contributing to disease stage and inflammation [160]. The increased expression of NKG2D on liver-infiltrating CD8+ T cells was also observed in chronic HBV and HCV infection, and likewise correlated in HCV infection with a higher activity of liver enzymes and a greater histological severity of liver injury [173,174]. Whereas NKG2D acts as a direct activator on NK cells, triggering cytotoxicity and cytokine secretion [175][176][177], Kennedy et al demonstrated that it is a co-stimulatory molecule acting in synergy with the TCR on HBV-specific CD8+ T cells, similar to other viral infections [174,178].…”
Section: Immunopathogenesis In Hbv/hdv Co-infectionmentioning
confidence: 98%